Building Independent Learning in Junior High School Students Through Training in Cloud-Based Digital Application Mastery - Nia Arfina Foci; Edo Kurnia; Tessa Zulenia Fitri; Rama Dani Eka Putra; M. Arif Munanda; Muhamad Yasin (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
This community service activity aims to improve the digital literacy of seventh-grade students at SMP Ar Risalah Islamic School Padang through training in cloud-based productivity applications. Initial observations indicate that most students still have limitations in utilizing digital technology for learning purposes. This program employed an educational-participatory intervention design, combining structured training with active learner involvement. The implementation followed three main stages: preparation, training delivery over two consecutive days in the school computer laboratory, and evaluation using pre-tests and post-tests. The training introduced students to Google Docs, Google Drive, and Canva as practical learning tools, while also promoting digital ethics aligned with Islamic values such as honesty, discipline, responsible technology use, and nationalism. Quantitative data were analyzed descriptively. The evaluation results show a significant improvement in students' digital knowledge and skills. The average cognitive pre-test score was 1.6 (out of 5), increasing to 3.8 on the post-test, representing an increase of 137.5%. The average practical skill score reached 7.6 out of 10. This activity proved effective in equipping students with basic digital skills and fostering positive attitudes toward productive and responsible technology use. This program is recommended for replication in other educational institutions to strengthen students' digital literacy from an early age.